Electromagnetic radiation from mobile phone causes no oxidative stress to the brain - Praputpittayaa C. (2014)
Background and objective: Although the electromagnetic radiation (EMR) emitted by mobile phones does not possess high energy like those of much higher frequencies such as X-rays and gamma-rays, several studies were reported with results showing that mobile phone use could produce hazardous health effects. These include headaches, changes in sleep patterns, electroencephalogram (EEG) and blood pressure. The present study was aimed to examine the effect of mobile phone exposure on brain oxidative stress. Methods: A group of about 300 g body weight male Wistar rats (EMR-exposed group) was put into re-straining cages and, after an equilibration periodof at least 30 minutes, was exposed to a 900 MHz electromagnetic signal from two mobile phones (GSM system) at less than 10 cm distance for one hour in a day. This exposure was repeated for one week. Another group of animals (control group) served as a control andwere subject to the same procedure but at more than 10 cm distancefrom the mobile phones. After the last exposure, the brains were removed, weighed and homogenized for determination of malondialdehyde (MDA) and glutathione (GSH). Results: The MDA concentrations inbrain homogenates of the animals in the EMR-exposed group were notdifferent from the control group of animals. Also, the GSH concentrations in the EMR-exposed group were at about the same levels as those in the control group. Conclusion: The present study providedno additional data indicating the probable role of oxidativestressin producing health effects of EMR exposure from mobile phone use.